A case of partial trisomy 3p syndrome with rare clinical manifestations - Dong Hoon Han; Ji Young Chang; Woo In Lee; Chong Woo Bae (Korean Pediatric Society, 2012)
Partial trisomy 3p results from either unbalanced translocation or de novo duplication. Common clinical features consist of dysmorphic facial features, congenital heart defects, psychomotor and mental retardation, abnormal muscle tone, and hypoplastic genitalia. In this paper, we report a case of partial trisomy 3p with rare clinical manifestations. A full-term, female newborn was transferred to our clinic. She had cleft lip-plate, dysgenesis of the corpus callosum, patent ductus arteriosus, pulmonary hypertension, and severe right-sided hydronephrosis, associated with ureteropelvic junction obstruction. Cytogenetic investigation revealed partial trisomy 3p; 46,XX,der(4)t(3;4) (p21.1;p16). The karyotype of her father showed a balanced translocation, t(3;4)(p21.1;p16). Therefore, the size of duplication can be an important factor.